A case study on comparison between wood truss and steel truss for roof structure - Muhammad Nur Ilyas , Amran Noor (2013)
Roof is an important structure found in all types of buildings regardless of size and shape. The using of wood trusses is widely used for generations before. With the growing construction on this time, there are other alternatives to replace wood truss that is widely use before with steel roof truss. Both have advantages and disadvantages respectively. Features such as workability, durability or strength, and suitability of the building will determine the type of truss to be used. Therefore, this study was undertaken to determine the truss suitable for use at this time. This approach is through questionnaires, observations, and the costs associated with the use of the two trusses. From this study, we can conclude that both have advantages and disadvantages truss, because they both have a lot different in terms of workability and the durability or strength. The results of research shows that the advantages mostly on using the steel truss. This difference makes them both special and acting as principle and the contractor or developer choice to build such a building.